KEBIJAKAN PEMANFAATAN DAN PENGAWASAN DALAM PENGELOLAAN SUMBER DAYA ALAM - Abubakar Sidik Katili (JURNAL LEGALITAS, 2009)
Environmental quality is resultant from various conditions which caused by event of in natures and also cause of activie of human. One of a real problems related to condition and environmental quality is management of natural resources. In management of natural resources, balance between exploitings and continuity is important prerequisite. Existence of exploiting of natural resources and environment having the character of eksploitatif will affect to environmental quality. Management of natural resources required some policies, two among others is exploiting policy and observation policy. In this article explained about the policies. Conclusion from this article; exploiting of natural resources and environment having the character of eksploitatif, causes the balance and continuity annoyed; required various strategic steps and. action according to development of natural resources and environmental; observation policy of natural resources is interpreted as straightening of law in environmental management and natural resources; coordination effort between between institute which related in exploiting of natural resources is required.